Strategi Lembaga Permasyarakatan dalam Menangani Pelanggaran Tata Tertib Oleh Warga Binaan (Studi pada Lapas IIB Lhoksukon) - Muhaddis Muhaddis; Amru Alba (Politeknik Kampar, 2025)
This research aims to find out and describe the strategy of correctional institutions in dealing with violations of rules and regulations by inmates at Lapas IIB Lhoksukon along with the obstacles and efforts. This research uses descriptive qualitative methods, obtaining data using observation, documentation and interview techniques. This research uses a purposive sampling technique to determine informants. The results of the research show that the strategy of correctional institutions in dealing with violations of rules and regulations by inmates at the IIB Lhoksukon Prison is in a persuasive way, namely consistently appealing to and informing inmates about the rules and regulations that apply in the prison and their consequences and carrying out activities to foster religious awareness and legal awareness as well as mental development. . The second method, namely repressive, means imposing disciplinary penalties on inmates who deliberately violate the rules and regulations in prison. Also carry out close supervision of all inmates who deliberately violate the rules and regulations in force in prison.